2019
DOI: 10.1080/15548627.2019.1586258
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy accounts for approximately one-third of mitochondrial protein turnover and is protein selective

Abstract: The destruction of mitochondria through macroautophagy (autophagy) has been recognised as a major route of mitochondrial protein degradation since its discovery more than 50 years ago, but fundamental questions remain unanswered. First, how much mitochondrial protein turnover occurs through autophagy? Mitochondrial proteins are also degraded by nonautophagic mechanisms, and the proportion of mitochondrial protein turnover that occurs through autophagy is still unknown. Second, does autophagy degrade mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 113 publications
(151 reference statements)
5
28
0
Order By: Relevance
“…In cultured mammalian cells, Burman et al (50) demonstrated selective mitophagic clearance of a mutant ornithine transcarbamoylase. Finally, Vincow et al (51,52), using Drosophila, found that mitophagy is protein selective in a whole animal system.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured mammalian cells, Burman et al (50) demonstrated selective mitophagic clearance of a mutant ornithine transcarbamoylase. Finally, Vincow et al (51,52), using Drosophila, found that mitophagy is protein selective in a whole animal system.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be necessary to assess whether and how MDVs regulate processed peptide efflux from mitochondria. autophagy, suggesting that pathways like MDVs or proteasomal degradation play a significant role in this regard 36 . Here we provide evidence that MDVs are indeed enriched in respiratory chain proteins in a mammalian system.…”
Section: Discussionmentioning
confidence: 99%
“…Piecemeal autophagy of mitochondrial subregions or fragments ( Fig. 2A) may also play a role in extreme cases of protein misfolding, and mitochondria-derived vesicles may directly target outer mitochondrial membrane proteins to lysosomes (16)(17)(18)(19).…”
Section: Quality Control Processes To Cope With Mitochondrial Burdensmentioning
confidence: 99%